2015
DOI: 10.1007/s00425-015-2417-y
|View full text |Cite
|
Sign up to set email alerts
|

Limited transpiration under high vapor pressure deficits of creeping bentgrass by application of Daconil-Action®

Abstract: First observation that chemical spray can induce limited-transpiration rate under high vapor pressure deficit. It appears that acibenzolar may be key in inducing this water conservation trait. Irrigation and water use have become major issues in management of turfgrasses. Plant health products that have been introduced into the turfgrass market have been observed to improve plant performance in water stress conditions. In this study, we evaluated whether a selection of common plant health products alter the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Our research has shown that controlling VPD can benefit protected cultivation systems 20,25–27 , similar to other findings 28,29 . However, most such studies focus on VPD levels below 4 kPa and few consider VPD up to or even beyond 5–6 kPa 30 , yet this represents the climate characteristics of most arid and semi-arid areas, such as northwest China. The highest VPD in a summer greenhouse in this region can be up to 6 kPa, but a suitable VPD for tomato growth is less than 2 kPa 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Our research has shown that controlling VPD can benefit protected cultivation systems 20,25–27 , similar to other findings 28,29 . However, most such studies focus on VPD levels below 4 kPa and few consider VPD up to or even beyond 5–6 kPa 30 , yet this represents the climate characteristics of most arid and semi-arid areas, such as northwest China. The highest VPD in a summer greenhouse in this region can be up to 6 kPa, but a suitable VPD for tomato growth is less than 2 kPa 31 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of metabolic pathways induced by ASM during pathogen attack, including anti-oxidant metabolism, have also been demonstrated to be activated during abiotic stress (Soylu et al, 2003). Several recent studies under field conditions have demonstrated that ASM improved heat and drought tolerance in creeping bentgrass (Shekoofa et al, 2015; Jespersen and Huang, 2016), and the improved drought performance of creeping bentgrass was associated with ASM-reduction of transpirational water loss (Shekoofa et al, 2015). The mode of action for ASM regulation of abiotic stress tolerance is still unclear and how it alters metabolic pathways to improve stress tolerance is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, VPD breakpoints for other species are also typically lower than what we observed in our study. For example, transpiration control occurred between 1.39 and 2.50 kPa in Agrostis stolonifera ( Shekoofa et al, 2016a ) in a study that demonstrated limited transpiration responses in high VPD environments can also be induced chemically. This could be partially due to the lower VPD environments that many plant species grow, and are therefore, tested in.…”
Section: Discussionmentioning
confidence: 99%